Economic Valuation of Mangrove Forest Ecosystem in Waidoba Island, South Kayoa District, South Halmahera Regency - M. Said Al Hadad; Ariyanti H. Fadel; Adi Noman Susanto; Salim Abubakar; Ardan Samman; Riyadi Subur (Jurnal Biologi Tropis, 2023)
Mangrove Forest ecosystems have distinctive characteristics and forms and have functions and benefits as development resources both as economic resources and ecological resources that have long been felt by the Indonesian people, especially for the people who live around that area. This research aims to identify the types of utilization of mangrove forest ecosystems and to analyze the total economic value of mangrove forest ecosystems in the area of Waidoba Island, South Kayoa District, South Halmahera Regency. The sampling method in this study used a purposive sampling method. Based on the results identification of the benefits and functions of the mangrove forest ecosystem in Waidoba Island area, Kayoa Selatan District, that there were (4) four types of mangrove forest ecosystem benefits, namely (1) direct benefits (2) indirect benefits, (3) optional benefits and (4) benefits of existence. While the results of costs and benefits of the total economic value of mangrove forest ecosystem in Waidoba Island area of South Kayoa District were obtained Rp. Rp.170.520.720.104/year or Rp.418.014.659,-/ha/year. This total economic value was the benefit value of mangrove forest ecosystem that utilized by the community covering an area of 407.93 Ha.